Forest conservation through protection of old growth: the case of Nova Scotia - Peter N. Duinker; Peter G. Bush; John C. Brazner; Mark C. MacPhail; Bruce J. Stewart; Emily K. Woudstra (The Forestry Chronicle, 2023)
Old-growth forests are both rare and special ecosystems across most of the world. Policies to protect and possibly enhance and increase them are plentiful and diverse across nations and sub-national jurisdictions. Nova Scotia has had a policy on conservation of old-growth forests on public lands in the province since 1999. The second such policy dated 2012 was recently replaced by a revised policy in 2022. After presenting knowledge based on selected scientific literature about old-growth forests in Nova Scotia, the paper describes the improvements made in the 2022 policy. These include: (a) a more-nuanced set of operational definitions; (b) a commitment to protect all old-growth forest on public lands, whether currently identified or not; (c) robust replacement provisions in the rare event that the provincial government chooses to allow provincially significant infrastructure to be built on public land supporting old-growth forest; and (d) a renewed commitment to work with private landowners on their aspirations to conserve old-growth forest. The new policy, adopted in August 2022, also contains a commitment to a public review and possible renewal by August 2027.